Życie kulturalne Zduńskiej Woli lat zaborów - Tomaszewska, Justyna (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2012)
The history of Zduńska Wola is mostly synonymous with the dynamic industrialization which began in the XIX century. The town became rapidly growing centre of textile industry. Poles, Germans and Jews were three nations who contributed to the town’s development. Multiethnic society provided cultural progress, first of all in the areas of music and theatre. In the second half of the XIX century artists and musicians started to appear in the town. The folk music was the most favored among industrial community. At the end of XIX century town’s citizens started to organize cultural life. As a result of cultural awareness, in the 1907 they established musical and drama association “Lutnia”. The aim of this organization was making culture enthusiast focus on drama and folk theme. Moreover, the charitable foundations came into being thanks to cultural sphere existence. All the activities in the community’s cultural development strengthened national consciousness and assimilate other nations into local customs, traditions and manner.